Carboplatin hypersensitivity induced by low-dose paclitaxel/carboplatin in multiple platinum-treated patients with recurrent ovarian cancer. Issue 2 (1st February 2005) - Watanabe, Y.; Nakai, H.; Ueda, H.; Nozaki, K.; Hoshiai, H.
Abstract : We report five cases of carboplatin (CBDCA) hypersensitivity after weekly low-dose paclitaxel (60 mg/m 2 )/CBDCA (area under the concentration curve = 2) therapy in patients with recurrent ovarian cancer receiving multiple platinum-based chemotherapy. Paclitaxel and CBDCA therapy was indicated as second-line chemotherapy in one patient and as third line in four patients with recurrent disease. The range of previously administered total CBDCA was 2582–9589 mg, and the CBDCA area under the concentration curve of the first treatment exhibited appropriate intensity (mean, 1.92 ± 0.10; range, 1.76–2.10) in all patients. However, one patient exhibited severe hypersensitivity reactions including cardiac arrest and apnea, and another four patients developed eruptions, hypotension, and tachycardia soon after administration of CBDCA. Our report suggested that CBDCA hypersensitivity was correlated with the total dose of previously administered platinum agents and that CBDCA should be excluded in patients who have received multiple platinum-based chemotherapy, even in platinum-sensitive cases, because CBDCA hypersensitivity can occur even with low-dose CBDCA administration.